Endometrial stromal beta-catenin is required for steroid-dependent mesenchymal-epithelial cross talk and decidualization - Zhang Ling; Patterson Amanda L; Zhang Lihua; Teixeira Jose M; Pru James K (Reproductive Biology and Endocrinology, 2012)
Abstract Background Beta-catenin is part of a protein complex associated with adherens junctions. When allowed to accumulate to sufficient levels in its dephosphorylated form, beta-catenin serves as a transcriptional co-activator associated with a number of signaling pathways, including steroid hormone signaling pathways. Methods To investigate the role of beta-catenin in progesterone (P4) signaling and female reproductive physiology, conditional ablation of Ctnnb1 from the endometrial mesenchymal (i.e. stromal and myometrial), but not epithelial, compartment was accomplished using the Amhr2-Cre mice. Experiments were conducted to assess the ability of mutant female mice to undergo pregnancy and pseudopregnancy by or through oil-induced decidualization. The ability of uteri from mutant female mice to respond to estrogen (E2) and P4 was also determined. Results Conditional deletion of Ctnnb1 from the mesenchymal compartment of the uterus resulted in infertility stemming, in part, from complete failure of the uterus to decidualize. E2-stimulated epithelial cell mitosis and edematization were not altered in mutant uteri indicating that the mesenchyme is capable of responding to E2. However, exposure of ovariectomized mutant female mice to a combined E2 and P4 hormone regimen consistent with early pregnancy revealed that mesenchymal beta-catenin is essential for indirectly opposing E2-induced epithelial proliferation by P4 and in some mice resulted in development of endometrial metaplasia. Lastly, beta-catenin is also required for the induced expression of genes that are known to play a fundamental role in decidualization such as Ihh, Ptch1, Gli1 and Muc1 Conclusions Three salient points derive from these studies. First, the findings demonstrate a mechanistic linkage between the P4 and beta-catenin signaling pathways. Second, they highlight an under appreciated role for the mesenchymal compartment in indirectly mediating P4 signaling to the epithelium, a process that intimately involves mesenchymal beta-catenin. Third, the technical feasibility of deleting genes in the mesenchymal compartment of the uterus in an effort to understand decidualization and post-natal interactions with the overlying epithelium has been demonstrated. It is concluded that beta-catenin plays an integral role in selective P4-directed epithelial-mesenchymal communication in both the estrous cycling and gravid uterus.